Drainage Planning in the Cities of Bangladesh: Case Study of Drainage and Water Logging in Chaktai Commercial area, Chittagong - Ashraf, M Ali; Chowdhury, Md Shariful Alam (Journal of Bangladesh Institute of Planners, 2012)
For quite some time, professional planning is being practiced in our cities. Unfortunately, drainage planning is the most neglected component of our city planning and management activities. Drainage engineering is done mostly on an ad hoc basis, often overtaking drainage planning. To understand the drainage problem of our cities, Chittagong in particular, Chaktai Commercial Area was identified as the case study area for further exploration and analysis. This case study examines the existing situation, assessing causes behind the problems, inquiring about the likings and disliking of the stakeholders, and identifying possible solutions as an essential input towards arriving at appropriate planning decisions. It identifies the guiding principles relating to the effective integration of a drainage network in the land use plan for the city. Considering physical characteristics, topography, catchment area and the routes of existing drainage channels, the urban area has been divided into 10 drainage areas. The Master plan sets out a staged development program of storm water, drainage and flood control works of the above drainage area up to the year 2015 to meet the Storm Water Drainage and Flood Control problems. Chaktai is the major seat of trade and commerce in Chittagong. It is observed that though Chaktai has lost its past glory as a national business centre controlling food business in the whole country, still it has retained its importance as a regional business hub and is continuing to contribute significantly to the national economy. The study thus helps us understand the nature, type and magnitude of the drainage and water logging problems faced by the city dwellers. The policy proposals and recommendations that are provided in the paper could be considered while preparing a land use plan for a city. DOI: http://dx.doi.org/10.3329/jbip.v2i0.9556 Journal of Bangladesh Institute of Planners Vol. 2, December 2009, pp. 49-60